The influence of reduced breathing during swimming on some respiratory and metabolic values in blood - Kapus, Jernej (Kinesiologia Slovenica, 2002)
The purpose of the present study was to ascertain the influence of reduced pulmonary ventilation on blood acid-base balance during swimming. Five trained swimmers (age 21plus minus2 years, height 187plus minus5 cm and weight 83plus minus 6 kg) volunteered to participate in this study. They had to swim 400 m front crawl at velocity VOBLA two times. Firstly, they were taking breath every two strokes (B2). During the second trial they swam the same distance at the similar velocity, however with reduced breathing frequency, taking breath every four strokes (B4). Measures included lactate concentration (LA) and parameters of blood acid-base status (pH, Posub2, Pcosub2) before and during the third minute after the exercise. There was only Pcosub2 significantly increased after B4 than after B2 (p<0.05). After the exercise other parameters (LA, pH, HCOsub3 and Posub2) did not change significantly in response to reduced breathing frequency during swimming. It may be concluded that the reduced breathing frequency during front crawl swimming at VOBLA velocity did not cause hypoxia nor increased LA. However, it increased the Pcosub2 to the range of hypercapnia.330
Keywords: dihanje; fiziologija; frekvenca dihanja; plavanje; raziskave